Reliability enhancement in petrochemical industry: an integrated RBD and FTA approach - Ariandi, Teuku; Away, Yuwaldi; Dirhamsyah, Dirhamsyah (Politeknik Negeri Lhokseumawe, 2025)
Turnaround maintenance plays an important role in the petrochemical industry, directly influencing production reliability and operational continuity. Unplanned shutdowns and service disruptions can result in significant economic losses, yet statistics show that nearly 80% of turnaround activities fail to achieve their performance targets in terms of time, cost, safety, quality, and environmental compliance. This study addresses these challenges by evaluating and enhancing the reliability of the ammonia production system at an Indonesian petrochemical company through an integrated approach combining the Reliability Block Diagram (RBD) and Fault Tree Analysis (FTA). RBD modeling was used to represent the production system as functionally arranged blocks, while FTA was applied to identify root causes of failures. Analysis using ReliaSoft BlockSim and Weibull++ revealed that the system’s reliability was only 0.029 over 5,000 hours, far below the target reliability of 0.9. The most critical components were identified as the Primary Reformer, Ammonia Compressor, and Syngas Compressor. Seven improvement scenarios were simulated, with results showing that the combination of preventive maintenance (PM) and load-sharing configuration yielded the most effective outcome. This approach improved reliability to 0.076 and availability to 0.812. The results show that a proactive, reliability-based maintenance strategy combined with system redundancy can substantially reduce risks of unscheduled shutdowns, extend turnaround intervals, and improve production uptime. Furthermore, the integrated RBD-FTA approach provides a robust framework for proactively identifying and addressing vulnerabilities in complex petrochemical systems.